Reducing Menarche-Related Anxiety Through Reproductive Health Education: A Quasi-Experimental Study - Rismayanti, Tetin; Badriah, Siti (STIKep PPNI Jawa Barat, 2025)
Background: Menarche is the first menstruation when a teenage girl enters puberty. Anxiety is the symptom that most often occurs in adolescent girls when facing menarche. Objective: To identify the influence of adolescent reproductive health education on anxiety about facing menarche in grade 7 and 8 female students at MTS Al Husna Gembor, Tangerang City. Method: Quasy Experimental with pre and posttest without control (without a control group), the researcher only intervened in one group without a comparison. The effect of treatment is assessed by comparing the pre-test scores with the post-test. The research sample was 54 respondents. Results: Before being given reproductive health education interventions, the majority of respondents experienced moderate anxiety (66.7%). After being given reproductive health education interventions, the majority of respondents experienced mild anxiety (66.7%). There is an influence of health education on the level of anxiety facing menarche in grade 7 and 8 female students at MTS Al Husna Gembor Tangerang (p: 0.000). Suggestion: It is hoped that health services, especially Community Health Centers, will increase health education and counseling activities that can increase adolescent knowledge regarding reproductive health, especially regarding menarche for adolescent girls. This is to increase the knowledge of young women so that they can reduce their anxiety levels when facing menarche.